Pharmacovigilance in healthcare education: students’ knowledge, attitude and perception: a cross-sectional study in Saudi Arabia - Monira Alwhaibi; Ghaida Alhindi; Majd Alshamrani; Maryam Bin Essa; Noha A. Al Aloola; Tariq M. Alhawassi (BMC Medical Education, 2020)
Abstract Background Medication safety and pharmacovigilance (PV) remains as an important discipline worldwide. However, there is a significant lack of knowledge of PV and adverse drug reaction (ADR) reporting among students in the healthcare field. Thus, this study is aimed to measure knowledge, attitude, and perceptions and compares it between healthcare students (i.e., medicine, dentistry, and nursing). Methods A cross-sectional study involving 710 undergraduate healthcare students from different universities in Saudi Arabia was conducted. A validated structured pilot-tested questionnaire was administered to the participants to assess their knowledge, attitude, and perceptions towards PV and ADRs reporting. Descriptive statistics were used to describe the study findings. Data were analyzed using SPSS version 21. Results Overall, the study found that 60.8 and 40.0% of healthcare students correctly defined PV and ADRs respectively. Most students showed positive attitudes and perceptions towards PV and ADRs reporting. PV knowledge, attitude, and perceptions towards PV were significantly higher among pharmacy students as compared to other healthcare students. Only 39% of healthcare students revealed that they have received any form of PV education and 49% of them indicated that PV is well covered in their school curriculum. Pharmacy students are more trained in their schools to report and have performed ADRs reporting in their school as compared to other healthcare students. Conclusions Pharmacy students have better knowledge, attitude, and perception towards PV and ADR reporting in comparison to other healthcare students. The study clearly describes the need for integrating pharmacovigilance education in Saudi healthcare schools’ curriculums to prepare them for real-world practices and workplaces.